The impact of vitamin D on the etiopathogenesis and the progression of type 1 and type 2 diabetes in children and adults - Li, Candong; Fu, Jiaowen; Ye, Yipeng; Li, Junsen; He, Yangli; Fang, Tuanyu (Frontiers in Endocrinology, 2024)
Diabetes is a common chronic metabolic disease with complex causes and pathogenesis. As an immunomodulator, vitamin D has recently become a research hotspot in the occurrence and development of diabetes and its complications. Many studies have shown that vitamin D can reduce the occurrence of diabetes and delay the progression of diabetes complications, and vitamin D can reduce oxidative stress, inhibit iron apoptosis, promote Ca2+ influx, promote insulin secretion, and reduce insulin resistance. Therefore, the prevention and correction of vitamin D deficiency is very necessary for diabetic patients, but further research is needed to confirm what serum levels of vitamin D3 are maintained in the body. This article provides a brief review of the relationship between vitamin D and diabetes, including its acute and chronic complications.